Hétérosexualités en action - Vulca Fidolini (Glad!, 2017)
By exploiting results from a qualitative study carried out in France on 23 young Moroccan and Muslim migrant men, between the ages of 20 and 30, this article analyses how heterosexuality expresses its normative power on gender identification processes. The paper focuses attention on constructions of masculinity in both homosocial and mixed contexts in order to describe how the production of heterosexual masculinities is also based on shaping “complementary” profiles of these hegemonic masculinities. In particular, we deal with the case of “predatory” masculinity as well as “complicit masculinities” which endorse and reaffirm the hegemonic power of the predatory one. This approach leads to analyse not only gender identification trajectories but also to observe how intra- and inter- cultural relations (e.g. between migrant and majority populations) or intra- and inter- generational relationships (e.g. between young people and adults) shape the experiences of the interviewees.